The effect of polarization separation on the performance of Candecomp/Parafac-based vector sensor array processing - Guo, Xijing; Miron, Sebastian; Brie, David (Physical communication, 2012)
In this paper we generalize the polarization separation measure introduced by Compton (1981) [2] for collocated sources, to the case of two sources with distinct DOAs recorded on a vector sensor array. We give a geometrical interpretation of this new measure and show that this polarization separation becomes essential for source estimation accuracy when the angular separation is insufficient.